Comparison between weekly cisplatin‐enhanced radiotherapy and cetuximab‐enhanced radiotherapy in locally advanced head and neck cancer: first retrospective study in Asian population. Issue 3 (3rd November 2016) - Rawat, Sheh; Ahlawat, Parveen; Kakria, Anjali; Kumar, Gaurav; Rangaraju, Ranga Rao; Puri, Abhishek; Pal, Manoj; Chauhan, Deepika; Devnani, Bharti; Chadha, Pranav
Abstract: Aim: To present a direct comparison between chemotherapy‐enhanced radiotherapy (CERT) and biotherapy‐enhanced radiotherapy (BERT) in locally advanced head and neck cancer. Methods: It is a retrospective analysis of 53 patients with locally advanced head and neck cancer treated from August 2006 to December 2008. For CERT, patients received weekly cisplatin (40 mg/m 2 ) and for BERT, a loading dose of 400 mg/m 2 of cetuximab given one week prior to radiotherapy followed by 250 mg/m 2 given weekly along with radiotherapy. Disease‐free survival (DFS) and overall survival (OS) were computed with Kaplan–Meier curve with log‐rank test for comparison between the two groups. Multivariate Cox proportional hazards regression analysis was performed to estimate the impact of known relevant prognostic factors on DFS and OS. Results: The median DFS was significantly better with CERT than BERT group (50.82 vs 11.66 months; P = 0.031). The 3 years DFS was significantly higher in CERT group than in BERT group (60.0% vs 14.3%; P = 0.022). The median OS was significantly better with CERT than BERT group (53.61 vs 32.55 months; P = 0.044). The 3 years OS was also significantly higher in CERT group than in BERT group (74.0% vs 42.1%; P = 0.032). There were no significant differences in acute toxicities of all grade and grade ≥3 between the two groups. The compliance to treatment and assisted feeding dependency for more than 6 months duration were also not significantly different. Conclusion: CERT is associated with better outcome with no significantly increased acute toxicities compared to BERT.